Alfred Riedl (2011). Didaktik der beruflichen Bildung, 2. komplett überarbeitete und erheblich erweiterte Auflage. - Gautschi, Peter; Schumacher, Irene (Swiss Journal of Educational Research, 2012)
Rezension